Bovine blood derived macrophages are unable to control Coxiella burnetii replication under hypoxic conditions - Mauermeir, Michael; Ölke, Martha; Hayek, Inaya; Schulze-Luehrmann, Jan; Dettmer, Katja; Oefner, Peter J.; Berens, Christian; Menge, Christian; Lührmann, Anja (Frontiers in Immunology, 2023)
Coxiella burnetii is a zoonotic pathogen, infecting humans, livestock, pets, birds and ticks. Domestic ruminants such as cattle, sheep, and goats are the main reservoir and major cause of human infection. Infected ruminants are usually asymptomatic, while in humans infection can cause significant disease. Human and bovine macrophages differ in their permissiveness for C. burnetii strains from different host species and of various genotypes and their subsequent host cell response, but the underlying mechanism(s) at the cellular level are unknown. Here, we confirmed that peripheral blood-derived human macrophages prevent C. burnetii replication under oxygen-limiting conditions. In contrast, oxygen content had no influence on C. burnetii replication in bovine peripheral blood-derived macrophages. In hypoxic infected bovine macrophages, STAT3 is activated, even though HIF1 is stabilized, which otherwise prevents STAT3 activation in human macrophages. In addition, the TNF mRNA level is higher in hypoxic than normoxic human macrophages, which correlates with increased secretion of TNF and control of C. burnetii replication. In contrast, oxygen limitation does not impact TNF mRNA levels in C. burnetii-infected bovine macrophages and secretion of TNF is blocked. As TNF is also involved in the control of C. burnetii replication in bovine macrophages, this cytokine is important for cell autonomous control and its absence is partially responsible for the ability of C. burnetii to replicate in hypoxic bovine macrophages. Further unveiling the molecular basis of macrophage-mediated control of C. burnetii replication might be the first step towards the development of host directed intervention measures to mitigate the health burden of this zoonotic agent.